PENGARUH HARGA KOMPETITIF, KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN DI PASAR HIGIENIS SELINDUNG PANGKALPINANG - Nurma Dwi Murtya; Jumhanadi Jumhanadi (LPPM STIE PERTIBA Pangkalpinang, 2020)
The research purpose is to analyze and determine the influence of Competitive Prices, Product Quality, and Location on Purchasing Decisions on consumers in the Selindung Pangkal Pinang Hygienic Market. The research variables consist of independent variables, namely: Competitive Prices, Product Quality, and Location while the dependent variable is Purchasing Decisions. Analysis of the data used is a multiple linear regression analysis followed by simultaneous and partial tests with the help of the SPSS program. The results of this study stated that simultaneously competitive price, product quality, and location variables had a positive and significant effect on purchasing decisions by 97.5%. Based on the t-test that the variable competitive prices, product quality, and location have a positive and significant effect on purchasing decisions. Hypothesis test results indicate the null hypothesis (H0) is rejected in all the variables tested, and alternative hypotheses (Ha) are accepted, meaning all independent variables consisting of competitive prices, product quality, and location affect the purchase decision.